Stability analysis of higher-order delta-sigma modulators using the describing function method - Lota, Jaswinder; Al-Janabi, Mohammed; Kale, Izzet (My University, 2006)
The aim of this paper is to determine the stability of higher-order ?;-? modulators using the Describing Function Method. The maximum stable input limits for third-, fourth- and fifth-order Chebyshev Type II based ?;-? modulators are established. These results are useful for optimising the design of higher-order ?;-? modulators. © 2006 IEEE.
ISCAS 2006: 2006 IEEE International Symposium on Circuits and Systems --
Keywords: Chebyshev approximation; Function evaluation; Optimization; System stability; Describing function methods; Maximum stable input; Delta sigma modulation